ANALYSIS OF REMAINING CONSTRUCTION MATERIALS AND THEIR CAUSAL FACTORS IN BUILDING PROJECT - Candra Yuliana; Elma Sofia; Gawit Hidayat; Munawarah (Jurnal Infrastruktur, 2024)
The problem that occurred in the ABC Flats Construction Project in Banjarbaru was that the project land was quite narrow. So if there is a large scale accumulation of material waste and lack of material management it can result in delays in the construction process, especially the mobilization and demobilization of tools. The aim of this research is to determine materials that cause large waste costs and the factors that cause them, as well as possible strategies to minimize waste. The analysis method is carried out using Pareto, waste cost and fishbone analysis. Collecting data by means of observation and interviews or brainstorming on several similar projects. The results of the Pareto analysis (80/20) show that there are two materials that contribute large costs, namely iron and concrete. The material that has the potential to generate large waste costs in the ABC Kalimantan Flats Construction Project as of the 21st week is ready mix concrete. The contribution of waste value per square meter is 0.073 m3 with a waste cost of 0.003% of the contract value. Based on the fishbone analysis, it was found thst the factors causing waste are a narrow location, stacking of moving materials, workers placing material carelessly, length of reinforcement that is not uniform, simplification of the shape of the pile cap structure, use of tools that do not match their function, number of orders that do not match, the rest of the concrete in the mixer, workers fatigue. Strategies to minimize waste of iron-concrete and ready-mix concrete materials are providing guidance to blacksmiths and workers, making access to tool distribution, using tools according to their functions, utilizing residual concrete, analyzing linear programs or barbending schedules. These results become considerations and suggestions in reducing the project budget due to the impact of material waste.